Philosophy of Education After the Golden Years - Jackson, Liz (Philosophical Inquiry in Education, 2024)
Philosophy of education’s relevance to schooling and value to society have always been contested within the field. When reading about the state of the field, one often gets the sense that philosophy of education is losing its cache, given the prevalence of data-oriented views about research. But the solution to this crisis is often difficult to identify. In this context, this essay investigates the prevalence of “golden years” thinking in the history of philosophy of education and what it would mean to think differently and go beyond this view. It explores how philosophy of education is framed as peripheral to mainstream educational research today and why students might not choose to study it. Then I examine precarity as a common discourse in history of the field. I scrutinize whether and how we are “in danger,” who “we” are, and the history of this imaginary. I conclude with reflections on moving on from these discourses in the future.